Graphene-based nano-materials for lithium–sulfur battery and sodium-ion battery. (July 2015) - Wu, Songping; Ge, Rongyun; Lu, Mingjia; Xu, Rui; Zhang, Zhen
Abstract: Graphene-based nano-materials have provided an opportunity for next-generation energy storage device, particularly for lithium–sulfur battery and sodium-ion battery (SIB), due to their unique properties. This review comprehensively summarizes the present achievements and the latest progress of inorganic nano-materials/graphene composites as the electrode materials for Li–S battery and SIBs. Electrochemical principles, performances and key obstructions of graphene-based materials in the actual application are considered. This review gathers and classifies updated knowledge about Li–S battery and SIB nanomaterials related to graphene, with the aim of offering a wide view of those systems. It is concluded that cost-effective SIBs and Li–S battery are promising next-generation battery candidates in the near future, but require further investigation and improvement to deal with some critical scientific issues. Graphical abstract: Graphene-based nano-materials have aroused considerable interest as electrode materials for lithium–sulfur battery and sodium-ion battery (SIB) due to their unique properties. The excellent electrochemical performances of graphene-based nanomaterials suggested that they are promising candidates for electrode materials in next-generation energy storage device. This article is a timely and powerful report, which comprehensively elaborates the present achievements, the latest progress and future advancement of graphene-based electrode materials for Li–S battery and SIBs. Highlights: Graphene-based nanomaterials for energy-storage device (Li–S battery and SIB). Electrochemical principles and performances of graphene-based materials are considered. Key obstructions and future development of novel materials were reviewed.